71. Use of Intravenous Immunoglobulin Therapy Reduces Progression to Mechanical Ventilation in COVID-19 Patients with Moderate to Severe Hypoxia. (31st December 2020) - Sakoulas, George; Geriak, Matthew; Kullar, Ravina; Greenwood, Kris; Habib, Mackenzie; Vyas, Anuja; Ghafourian, Mitra; Dintyala, Venkata Naga Kiran; Haddad, Fadi
Abstract: Background: The majority of COVID-19 morbidity and mortality occurs in patients who progress to mechanical ventilation. Therefore, therapeutic interventions targeting the mitigation of this complication would markedly improve outcomes and reduce healthcare utilization. Methods: Patients with COVID-19 from two hospitals in San Diego, California were randomized at a 1:1 ratio to receive standard of care (SOC) plus intravenous immunoglobulin (IVIG) at 0.5 g/kg/day x 3 days with solumedrol 40 mg 30 minutes before infusion (IVIG group) versus SOC alone. The primary composite endpoint was receipt of mechanical ventilation or death before receiving ventilation. Patients were followed until discharge to home or up to 30 days from time of enrollment. Results: Sixteen patients received IVIG plus SOC and 17 SOC alone. The median age was 54 years for SOC and 57 years for IVIG. Median time from hospital admission to study enrollment was 1 day (range 0–4) for SOC and 2 days (range 0–8) for IVIG. APACHE II scores and Charlson comorbidity indices were similar for IVIG and SOC (median 8 vs 7 and 2 for both, respectively). Seven SOC patients achieved the composite endpoint (6 ventilated, 1 death) versus 2 IVIG patients (2 ventilated), p=0.12, Fisher exact test. Among the subgroup with an estimated A-a gradient of >200 mm Hg at time of enrollment, the IVIG group showed a lower rate of progression to the composite endpoint (2/14 vs 7/12, p=0.04 Fisher exact test), shorter median hospital length (11 vs 24 days, p=0.001 Mann Whitney U), and shorter median intensive care unit (ICU) stay (3 vs 13 days, p=0.005 Mann Whitey U). Conclusion: This small, prospective, randomized, open-label study showed that when administered to hypoxic non-ventilated COVID-19 patients with an A-a gradient of >200 mm Hg (corresponding to a requirement of 6 liters O2 via nasal cannula to achieve an SpO2 of 92%), IVIG significantly decreased the rates of progression to mechanical ventilation, ICU length of stay, and total hospital length of stay. A Phase 3 prospective, randomized, placebo-controlled, multicenter trial is underway to further validate these findings. Disclosures: George Sakoulas, MD, Octapharma (Grant/Research Support, Scientific Research Study Investigator)